Electrooxidation of 4-Methylcatechol in the Presence of Azide Ion and Its Kinetic Study by Digital Simulation - Ojani, Reza; Raoof, Jahan-Bakhsh; Hosseinzadeh, Rahman; Alinezhad, Ali (Asian Journal of Chemistry, 2010)
The electrooxidation of 4-methylcate-chol has been studied in the presence of azide ion (N3–) as a nucleophile in aqueous solution using cyclic voltammetry and differential pulse voltammetry. Multicyclic voltammetry of 4-methylcatechol indicates one anodic peak and corresponding cathodic peak without any polymerization. Cyclic voltammogram of 4-methylcatechol in the presence of azide ion shows one enhanced anodic peak and decreased corresponding cathodic peak in acidic solution. However, in the neutral solution, cyclic voltammograms show one anodic and two cathodic peaks. Effects of some parameters such as scan rate and azide ion concentration on the shape of cyclic voltammograms were investigated. Also, the cyclic voltammograms of 4-methylcatechol in the presence of azide ion in acidic and neutral solutions were digitally simulated based on EC' and ECE mechanisms, respectively. The observed catalytic rate constant (kcat) for catalytic reaction and homogeneous rate constant (km) for Michael addition reaction were estimated by comparing the experimental cyclic voltammetric responses with the digitally simulated ones.